NEW ASTRONOMICAL STATION ON MOUNT DUSHAK-EREKDAG. II. A DUAL CHANNEL PHOTOMETER. - Dorokhov, N. I.; Dorokhova, T. N. (Одеські астрономічні публікації, 2017)
A dual-channel photometer has been constructed at Astronomical Observatory of Odessa State University to observe two astronomical objects simultaneously. The photometer has been attached to 0.8 m in diameter Ritchey-Chretien system telescope at a station of Odessa Observatory on the Mount Dushak-Erekdag in Turkmenistan. The equipment works in normal observing mode. Light curves of observations are presented.